PENENTUAN PENJADWALAN DAN DISTRIBUSI PRODUK YANG OPTIMAL MENGGUNAKAN MODEL VEHICLE ROUTING PROBLEM DENGAN METODE SAVING MATRIX, SEQUENTIAL INSERTION DAN NEAREST NEIGHBOUR DI PT XYZ - Melva Asionna (2020)
The problem in transportation is the Vehicle Routing Problem (VRP). One type of Vehicle Routing Problem (VRP) is Capacitated Vehicle Routing Problem (CVRP), which is VRP which has a limited capacity of the vehicle. Daily delivery scheduling at PT XYZ based on the orders that exist for each day. Daily shipping routes will differ according to orders from customers. Because of the uncertain number of requests, there are times when vehicle capacity is insufficient and there are times when it is not fully utilized. The purpose of writing this Final Project is to form a VRP model for distribution routes at PT XYZ, solve it using a saving matrix, sequential insertion and nearest neighbor, and find out the most effective VRP settlement of the three methods. The saving matrix method uses savings. The sequential insertion method has advantages in determining the insertion location, while the nearest neighbor method considers the closest distance. Based on calculations performed in completing VRP using the matrix saving method, a total mileage of 2,061.95 km was obtained, with the sequential insertion method a total distance of 2,322.85 km was obtained, and with the nearest neighbor method a total mileage of 2,365.45 km was obtained. While the company's total mileage is 3,140.9 km. This shows that the saving matrix method is more effective in determining the distribution route at PT XYZ.